2009
DOI: 10.1111/j.1440-1754.2008.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Four‐country surveillance of intestinal intussusception and diarrhoea in children

Abstract: Intussusception in the four participating countries exhibited no seasonal trend. We found that it is feasible to establish a surveillance network for intussusception in developing countries. Future efforts must define population base before the introduction of rotavirus vaccine and continue for some years thereafter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…In our study, nearly 50% of children with recurrence of intussusception were younger than one year at the first episode and it decreased to 7.9% in older children. 71% of recurrences developed within 6 months of the initial onset, thus it can be concluded that intussusception is more common in the first year of life and the recurrence of intussusception decreases after the toddler period, that is consistent with some other studies ( 10 , 25 , 33 , 35 , 36 ). There were controversies about seasonal variation of the occurrence of intussusception.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, nearly 50% of children with recurrence of intussusception were younger than one year at the first episode and it decreased to 7.9% in older children. 71% of recurrences developed within 6 months of the initial onset, thus it can be concluded that intussusception is more common in the first year of life and the recurrence of intussusception decreases after the toddler period, that is consistent with some other studies ( 10 , 25 , 33 , 35 , 36 ). There were controversies about seasonal variation of the occurrence of intussusception.…”
Section: Discussionsupporting
confidence: 88%
“…There is considerable documentation of a marked diversity in seasonality of not only rotavirus but also of the rotavirus strains in circulation because of the variation in humidity and temperature across the country. The majority of rotavirus diarrhoea cases have been reported to occur between 6 and 12 months of age [22], but in developing countries rotavirus diarrhoea has been reported to be prevalent in younger children [23,24], data that are corroborated by our study: 79.7% of rotavirus-positive cases were found to be <1 year old and 58.2% cases were <7 months old. A meta-analysis of three observational studies in developing countries has shown that breast-fed children <6 months old are 6.1 times less likely to die of diarrhoea than infants who are not breast fed [25].…”
Section: Discussionsupporting
confidence: 86%
“…We reviewed 2757 abstracts to identify a total of 113 potential full-text articles and 1 meeting abstract, from which 82 studies met the inclusion criteria for our analysis (Figure 1; Table 1) [11][91]. We excluded 31 articles due to non-English language (n = 8), duplicate data (n = 14), non-epidemiology study or review (6), included in previous review (2), or age <1 excluded (1).…”
Section: Resultsmentioning
confidence: 99%